Environment-friendly material for repairing pavement inspection well seat and use method of environment-friendly material

By developing an environmentally friendly repair material containing organic compounds A and B, and adding nano calcium carbonate and antioxidants, the problem of single or unbalanced performance of the well seat repair material is solved, and the performance improvement is achieved in multiple aspects, extending the service life of the well seat and reducing maintenance costs.

CN119529588AInactive Publication Date: 2025-02-28BEIJING SHENGAN ZHUDA TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411852375.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In existing road projects, the inspection well seats are prone to damage such as cracks, damage, subsidence, etc. Due to long-term impact of vehicle crushing and environmental erosion, the inspection well seats are prone to damage such as cracks, damage, subsidence, etc. The existing restoration materials are insufficient in terms of strength, flexibility, durability, etc., and lack innovation.

Method used

Develop an environmentally friendly road surface inspection well seat repair material, using organic compound A (mercaptophenyl alcohol) and organic compound B (aminooctyl etheramine) as the main components, and adding nano calcium carbonate and antioxidants to form high-performance repair material through reasonable proportioning and process control.

Benefits of technology

The restoration material performs excellently in strength, flexibility, heat resistance, water resistance, adhesion and weather resistance, and can better adapt to the complex working environment and performance requirements of the inspection well seat, extend the service life of the inspection well seat and reduce road maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190917080000131
    Figure BDA0005190917080000131
Patent Text Reader

Abstract

The invention relates to the field of material engineering, in particular to an environment-friendly material for repairing a pavement inspection well seat and a use method of the environment-friendly material. A compound A, a compound B, nano calcium carbonate and an antioxidant which are mixed in proportion are fully stirred for 8-10 minutes on a construction site to be uniformly dispersed; and then pouring into a special mold or directly smearing on the repaired part of the inspection well seat with the smearing thickness of 2-4cm, and ensuring that the material is tightly attached to the surface of the original inspection well seat without bubbles and gaps.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of road engineering materials, and in particular to an environmentally friendly material for repairing a road surface inspection well seat and a use method thereof. Background Art

[0002] In road engineering, manhole seats are prone to damage such as cracks, breakage, and subsidence due to long-term vehicle crushing, environmental erosion and other factors. Although some existing new repair materials have improved some performance, they still do not fully meet the special needs of manhole seat repair. For example, some materials only focus on improving strength, but ignore the balance between flexibility and durability; or they are insufficient in terms of weather resistance and adhesion with different materials. Moreover, the compounds used in many repair materials have been widely studied and applied, lack of innovation, and it is difficult to fundamentally solve existing problems. Therefore, it is urgent to develop an environmentally friendly, efficient and comprehensive manhole seat repair material based on new organic compounds. Summary of the invention

[0003] The present invention provides an environmentally friendly road inspection well seat repair material and a use method, wherein the material comprises an organic compound A and an organic compound B, wherein the organic compound A is a compound having a chemical formula of C 10 H 12 O 3 The organic compound B is a thiol phenyl ester alcohol of the chemical formula C 12 H 27 The molecular structure of aminooctyl ether amine of NO includes amino group, ether bond and long-chain alkyl group.

[0004] The mercaptophenyl ester alcohol is prepared by reacting p-mercaptophenol with methyl acrylate in an organic solvent in the presence of an alkaline catalyst, the reaction temperature is controlled at 40-60° C., and the reaction time is 3-5 hours.

[0005] The aminooctyl ether amine is prepared by reacting n-octanol and ethanolamine as raw materials under the action of an acidic catalyst under reflux conditions, the reaction temperature is about 120-140° C., and the reaction time is 6-8 hours.

[0006] The repair material also includes nano calcium carbonate, the particle size of which is 20-50 nm, and the added amount is 5-10% of the total mass of the mixture of compound A and compound B.

[0007] The repair material also includes an antioxidant, which is a hindered phenol antioxidant, and the added amount is 0.5-1% of the total mass of the mixture of compound A and compound B.

[0008] The mixing ratio of the compound A and the compound B is 3:2-4:1.

[0009] The organic compound A can be replaced by the following components in mass ratio: 60-80 parts of bio-based polyol, 10-20 parts of short-chain polyether, 10-20 parts of epoxy-modified polyether, and 1-5 parts of water absorbent; the organic compound B is replaced by modified MDI with an NCO mass fraction of 28-30%.

[0010] The present invention also provides a method for repairing a road inspection well seat with an environmentally friendly repair material, comprising a pretreatment step: using a high-pressure air spray gun to remove dust, debris and loose particles on the surface of the inspection well seat, using a special cleaning agent to clean the surface oil, and then rinsing it with clean water and drying it.

[0011] It also includes material mixing and construction steps: stir the compound A and compound B, nano calcium carbonate and antioxidant mixed in proportion at the construction site for 8-10 minutes to make them evenly dispersed, then pour them into a special mold or directly apply them to the repaired part of the inspection manhole seat with a thickness of 2-4 cm, and ensure that the material fits tightly to the surface of the original inspection manhole seat without bubbles and gaps.

[0012] It also includes curing and maintenance steps: after the repair material is applied, it will naturally cure at room temperature for 12-24 hours. Avoid external interference during the curing period, and maintain for 1-2 hours after curing.

[0013] The repair material is used to repair the manhole seat that causes vibration, vehicle jumping, and height difference between the manhole cover and the manhole seat due to vehicle rolling, environmental erosion, etc., to improve the strength, flexibility, heat resistance, water resistance, adhesion and weather resistance of the repaired manhole seat, extend the service life of the manhole seat and reduce road maintenance costs

[0014] Beneficial technical effects:

[0015] The mercapto group, benzene ring and ester group in compound A and the amino group, ether bond and long-chain alkyl group in compound B achieve comprehensive improvement in the strength, flexibility, heat resistance, water resistance, adhesion and weather resistance of the repair material through their respective functional characteristics and mutual synergy, effectively overcoming the problem of single or unbalanced performance of traditional repair materials, and can better adapt to the complex working environment and performance requirements of the inspection well seat. The synthesis methods of compound A (mercaptophenyl ester alcohol) and compound B (aminooctyl ether amine) are elaborated in detail. By accurately controlling the reaction conditions, raw material ratio and other parameters, high-purity target compounds can be stably prepared, providing reliable technical guarantee for the large-scale production of repair materials. This synthesis method has the advantages of easy raw materials, relatively simple operation and controllable cost, which is conducive to industrial production and promotion and application. Material formulation and performance optimization: The performance of the repair material is further optimized by reasonably determining the mixing ratio of compound A and compound B and adding additives such as nano calcium carbonate and antioxidants. Nano calcium carbonate acts as a reinforcing agent to improve the strength and hardness of the material, while antioxidants significantly enhance weather resistance, enabling the repair material to maintain good performance stability during long-term use, extending the service life of the repaired manhole seat, reducing the frequency of repairs, and lowering road maintenance costs. DETAILED DESCRIPTION

[0016] Example 1

[0017] 1. Composition of repair materials Organic compound A: Mercaptophenyl ester alcohol: Its chemical structure contains mercapto (-SH), benzene ring and ester group (-COO-). The chemical formula is C 10 H 12 O 3 S. The mercapto group has a strong reactivity and can react chemically with other active groups in the repair material to form a cross-linked structure, thereby improving the strength and stability of the material. The presence of the benzene ring gives the material good rigidity and heat resistance, making it less likely to deform under high temperature conditions. The ester group enhances the flexibility and weather resistance of the material and reduces aging and cracking of the material due to environmental factors. In addition, the ester group also has a certain degree of adhesion, which helps to combine the repair material with the surface of the manhole seat. The synthesis method of compound A is as follows: First, para-mercaptophenol (C 6 H 6 OS) and methyl acrylate (C 4 H 6 O 2 ) is reacted in an organic solvent (such as ethanol) in the presence of an alkaline catalyst (such as sodium hydroxide). The reaction temperature is controlled at 40-60°C and the reaction time is 3-5 hours. During the reaction, the mercapto group in p-mercaptophenol reacts with the carbon-carbon double bond in methyl acrylate to generate compound A.

[0018] Another organic compound B, whose molecular structure contains an amino group (-NH 2 ), ether bonds (-O-), and long-chain alkyl groups (such as -C 8 H 17 ). The chemical formula is C 12 H 27 NO. It can react with the thiol or other possible active groups in compound A to further promote the formation of a cross-linked network and improve the strength and integrity of the material. The introduction of ether bonds increases the flexibility and water resistance of the material, allowing the material to maintain good performance in a humid environment. The long-chain alkyl provides good lubricity and hydrophobicity, reduces the surface energy of the material, and reduces the adhesion of dust and moisture. At the same time, the presence of long-chain alkyl also helps to improve the impact resistance of the material, so that it can better withstand the impact of vehicle driving. The synthesis steps of compound B are as follows: n-octanol (C 8 H 18 O) and ethanolamine (C 2 H 7 NO) as raw material, react under reflux conditions under the action of an acidic catalyst (such as sulfuric acid). The reaction temperature is about 120-140°C, and the reaction time is 6-8 hours. During the reaction, the hydroxyl group in n-octanol and the amino group in ethanolamine undergo a dehydration condensation reaction to generate compound B.

[0019] Compound A and compound B are mixed in a certain ratio (such as 3:2-4:1). At the same time, in order to further optimize the material properties, a small amount of nano calcium carbonate (particle size of 20-50nm) is added as a reinforcing agent, and the addition amount is 5-10% of the total mass of the mixture. Nano calcium carbonate can serve as a physical crosslinking point to improve the strength and hardness of the material. A certain amount of antioxidant (such as hindered phenol antioxidant) is also added, and the addition amount is 0.5-1% of the total mass of the mixture to enhance the weather resistance of the material and prevent the material from aging due to oxidation during long-term use.

[0020] 2. Usage method Pretreatment steps: Clean the inspection well seat to be repaired thoroughly, and use a high-pressure air spray gun to remove dust, debris and loose particles on the surface. Then use a special detergent to clean the surface oil, rinse with clean water and dry. Material mixing and construction steps: Mix the compound A and compound B mixed in proportion and the added nano calcium carbonate and antioxidant at the construction site. Use a high-speed stirring device to stir for 8-10 minutes to evenly disperse the components. Pour the mixed repair material into a special mold or apply it directly to the repaired part of the inspection well seat. When using the smearing construction, use a scraper or trowel to spread the material evenly on the surface. The thickness is determined according to the degree of damage and design requirements of the inspection well seat, generally 2-4 cm. During the smearing process, ensure that the material fits tightly with the original inspection well seat surface to avoid bubbles and gaps. Curing and maintenance steps: After the repair material is applied, it is naturally cured at room temperature. Due to the chemical reaction between the active groups in compound A and compound B, a stable cross-linked structure is gradually formed. The curing time is about 12-24 hours, and the specific time is affected by factors such as ambient temperature and humidity. During the curing period, the repaired part should be prevented from being disturbed by external forces, such as vehicle rolling and pedestrian trampling. After the curing is completed, the repaired part is maintained for 1-2 hours.

[0021] Two new organic compounds A (mercaptophenyl ester alcohol) and B (aminooctyl ether amine) were developed for use in manhole seat repair materials. Their unique group combinations have not been reported at home and abroad. The mercapto group, benzene ring and ester group in compound A and the amino group, ether bond and long-chain alkyl group in compound B have achieved comprehensive improvements in the strength, flexibility, heat resistance, water resistance, adhesion and weather resistance of the repair material through their respective functional characteristics and mutual synergy, effectively overcoming the problem of single or unbalanced performance of traditional repair materials, and can better adapt to the complex working environment and performance requirements of the manhole seat.

[0022] The synthesis methods of compound A (mercaptophenyl ester alcohol) and compound B (aminooctyl ether amine) are described in detail. By precisely controlling the reaction conditions, raw material ratio and other parameters, high-purity target compounds can be stably prepared, providing reliable technical support for the large-scale production of repair materials. This synthesis method has the advantages of easy availability of raw materials, relatively simple operation, and controllable costs, which is conducive to industrial production and promotion and application. Material formulation and performance optimization: By reasonably determining the mixing ratio of compound A and compound B, and adding additives such as nano-calcium carbonate and antioxidants, the performance of the repair material is further optimized. Nano-calcium carbonate, as a reinforcing agent, improves the strength and hardness of the material, and antioxidants significantly enhance the weather resistance, so that the repair material can maintain good performance stability during long-term use, extending the service life of the manhole seat after repair, reducing the frequency of maintenance, and reducing the cost of road maintenance.

[0023] Example 2

[0024] Preparation of repair materials for urban road inspection well seats: Synthetic organic compound A (mercaptophenyl ester alcohol): 10 grams of p-mercaptophenol and 8 grams of methyl acrylate are reacted in an ethanol solution at 50°C for 4 hours in the presence of 0.5 grams of sodium hydroxide catalyst to obtain compound A. Synthetic organic compound B (aminooctyl ether amine): 12 grams of n-octanol and 5 grams of ethanolamine are refluxed at 130°C for 7 hours under the action of 0.3 grams of sulfuric acid catalyst to obtain compound B. Compound A and compound B are mixed in a ratio of 3:2, and 8% mass fraction of nano calcium carbonate and 0.8% mass fraction of hindered phenol antioxidant are added, and they are evenly dispersed by high-speed stirring for 9 minutes. Repair construction: Pretreatment: Clean the surface of the inspection well seat with a high-pressure air spray gun and a detergent, fill large defects with repair mortar, and dry. Material mixing and construction: After mixing the prepared repair material for 9 minutes, pour it into a mold and place it on the repair part of the inspection well seat so that the material fits tightly with the original surface with a thickness of 3 cm. Curing and maintenance: Natural curing at room temperature for 18 hours, avoiding external interference during this period.

[0025] Example 3

[0026] Organic compound A: 4-hydroxy-3-methyl-2-pentanone (C 10 H 16 O 2 ) in this molecular structure, contains a carbonyl group (C=O) located on the second carbon atom, a hydroxyl group (-OH) attached to the fourth carbon atom, and a methyl group (-CH 3 ).

[0027] This organic compound A contains functional groups such as carbonyl (C=O) and hydroxyl (-OH), which play a vital role in the repair material. The carbonyl group has a strong polarity and can increase the adsorption of the compound to the surface of the well seat substrate. Specifically, the carbonyl group can form a weak chemical bond with components such as metal oxides on the surface of the substrate. Although this chemical bond is relatively weak, it is sufficient to significantly improve the adhesion between the material and the substrate, providing a good foundation for the adhesion of the repair material to the surface of the well seat. The hydroxyl group has good hydrophilicity, which enables the material to better contact and interact with the substrate in a humid environment. In actual application scenarios, the environment around the road inspection well seat is often more complex, and there may be groundwater seepage or rainwater accumulation. The hydrophilicity of the hydroxyl group ensures that the material can fit tightly to the substrate even in humid conditions. It is also conducive to the subsequent mixing uniformity with other components to ensure the consistency of the overall performance of the repair material.

[0028] Inorganic filler: Quartz sand: Quartz sand with appropriate fineness is selected as an inorganic filler, and its main function is to fill and strengthen. Quartz sand particles can be filled in the network structure formed by organic compound A, increasing the density and bearing capacity of the material. Through reasonable particle size matching and filling ratio, quartz sand can effectively improve the overall strength of the repair material, enabling it to better withstand the pressure brought by road vehicle loads and prevent the repaired parts from deformation or damage during use.

[0029] Additives: dispersants, defoamers, etc.: including dispersants, defoamers and other additives. The function of the dispersant is to ensure that the components can be evenly dispersed during the mixing process to avoid agglomeration, thereby ensuring the uniformity of the performance of the repair material. The defoamer is used to eliminate bubbles that may be generated during the mixing and construction process, because the presence of bubbles will reduce the density and strength of the material and affect the repair effect. These additives work synergistically to improve the construction performance of the material, ensure that the material can be evenly distributed during the application or injection process, and successfully complete the repair of the inspection well seat.

[0030] Organic compound A is the key active ingredient of the repair material of this solution. The synergistic effect of its carbonyl and hydroxyl groups is the core mechanism for achieving good repair effects. The polarity of the carbonyl group enables it to interact with the active sites on the surface of the manhole base. This interaction is similar to a weak chemical adsorption. By chemically bonding with components such as metal oxides on the surface of the base, the initial adhesion of the material to the base is enhanced. During the curing process of the material, this initial adhesion can provide a stable foundation for subsequent curing reactions and structure formation, ensuring that the repair material can be firmly attached to the surface of the manhole base. On the one hand, the hydroxyl group enhances the adaptability of the material in a humid environment. On the other hand, during the curing process of the material, it can undergo a certain degree of chemical reaction or physical cross-linking with other components. For example, the hydroxyl group may undergo a condensation reaction with the silanol (-SiOH) on the surface of the inorganic filler quartz sand to form a silicon oxygen bond (-Si-O-), thereby further consolidating the internal structure of the material and improving its overall strength and durability. At the same time, the presence of hydroxyl groups also makes the material have a certain degree of flexibility, which can adapt to the slight deformation of the road inspection manhole base under the action of vehicle load to a certain extent, avoiding cracking due to excessive rigidity of the material.

[0031] The inorganic filler quartz sand is filled in the network structure formed by the organic compound A in the material, increasing the density and load-bearing capacity of the material. It and the organic compound A jointly build a stable three-dimensional structure through physical filling and possible chemical interactions (such as the condensation reaction of hydroxyl and silanol mentioned above), so that the repair material has sufficient strength to withstand various loads on the road surface.

[0032] The role of the additive is to optimize the construction performance of the material and ensure the smooth progress of the repair process. The dispersant ensures that the components are evenly dispersed, and the defoamer eliminates bubbles. Their combined effect allows the repair material to be evenly and smoothly applied or poured into the damaged or cracked parts of the inspection well seat during the construction process, and to form a uniform and dense repair structure after curing, thereby improving the quality of the repair.

[0033] Organic compound B: 3,4-dihydroxybutyric acid ethyl ester (C 12 H 20 O 3 ): In this molecular structure, there is an ester group (-COO-) connected between the second carbon atom and the third carbon atom, and two hydroxyl groups (-OH) are respectively connected to the third carbon atom and the fourth carbon atom.

[0034] The organic compound B contains an ester group (-COO-) and two hydroxyl (-OH) functional groups. The ester group has a certain flexibility and can give the repair material a good elastic deformation ability. When the road inspection manhole seat is subjected to vehicle load, the ester group can deform to a certain extent through its own flexible structure without breaking, thereby dispersing the stress to the entire repair material system and avoiding local stress concentration leading to material cracking. This elastic deformation ability is crucial for the inspection manhole seat repair material that is under traffic load for a long time, and can effectively extend the service life of the repair structure.

[0035] Fiber reinforcement material: Chopped glass fiber: Chopped glass fiber is selected as fiber reinforcement material, which can form a three-dimensional network structure in the material, enhance the tensile and shear resistance of the material, and improve the overall mechanical properties of the repair material. Glass fiber has the characteristics of high strength and high modulus, and can play the role of skeleton support in the repair material, and synergize with organic compound B and other components to jointly improve the strength, toughness and durability of the repair material.

[0036] Additives: dispersants, defoamers, etc.: also include dispersants, defoamers and other additives, their role is the same as solution one, that is, to ensure the good construction performance of the material, to ensure that the components are evenly dispersed during the mixing process, to eliminate bubbles generated during stirring and construction, so that the repair material can be successfully used in the repair work of the inspection manhole seat.

[0037] For organic compound B, the presence of the ester group is the key to giving the material elasticity. The chemical structure of the ester group enables it to undergo a certain degree of flexible deformation when subjected to external forces. This deformation characteristic makes the repair material less likely to crack when subjected to deformation caused by road vehicle loads. When the vehicle load acts on the repaired part of the manhole seat, the ester group can buffer and disperse the stress through its own deformation, transferring the stress to the entire repair material system, thereby protecting the integrity of the repair structure.

[0038] In addition to their role in wet environment adaptability and curing, the two hydroxyl groups can also undergo a certain physical adsorption with the surface of the fiber-reinforced material, further enhancing the bonding between the material and the fiber, allowing the fiber to better play its reinforcing role. Specifically, the hydroxyl group may hydrogen bond with the hydroxyl group on the surface of the glass fiber (the glass fiber may carry a certain amount of hydroxyl group during the production process). This hydrogen bonding enhances the connection strength between the material and the fiber, allowing the fiber to play a more solid reinforcing role in the material, and together improve the overall performance of the repair material.

[0039] The fiber-reinforced material, chopped glass fibers, build a three-dimensional network structure in the material, which works with organic compound B and other components to improve the strength, toughness and durability of the repair material. The network structure formed by the glass fibers provides strong support for the repair material, enabling it to withstand greater loads and deformations. At the same time, combined with the elastic deformation capacity of organic compound B, the repair material not only meets the strength requirements, but also has good toughness and elasticity, and can better adapt to the complex stress conditions of the road inspection manhole seat. The additives ensure that the material can be evenly and smoothly applied to the repaired part of the inspection manhole seat during the construction process. The dispersant ensures that the components are evenly dispersed, and the defoamer eliminates bubbles, so that the repair material can be evenly distributed during the application or injection process, avoiding local defects and improving the quality of the repair.

[0040] First, clean the damaged or cracked parts of the manhole seat, remove the surface debris, dust, loose concrete, etc., to expose the solid substrate surface. This step is crucial because only when the repair is performed on a clean and solid substrate surface can a good bond between the repair material and the substrate be guaranteed. This can be done by high-pressure water gun flushing, wire brush cleaning, etc. For stubborn stains or debris, appropriate detergents can also be used for auxiliary cleaning. After cleaning, ensure that the substrate surface is dry to prevent moisture from adversely affecting the bonding and curing of subsequent repair materials.

[0041] According to a certain ratio (e.g. organic compound A: inorganic filler: additive = 3:5:2), the organic compound A, quartz sand and additives are fully stirred and mixed in a stirring device. The stirring time is controlled within 5-10 minutes to ensure that the components are evenly distributed to form a repair material slurry with good construction performance. During the stirring process, attention should be paid to the control of the stirring speed to avoid too fast stirring speed causing material splashing or too many bubbles, and it should not be too slow to avoid uneven mixing of the components. First, put the organic compound A and the additives into the stirring device, turn on the stirring function to make them initially mixed evenly, and then gradually add quartz sand, and continue to stir until the components are completely evenly mixed to form a uniform slurry state. According to the ratio (e.g. organic compound B: fiber reinforcement material: additive = 4:3:3), the organic compound B, chopped glass fiber and additives are stirred in a suitable stirring device at a moderate stirring speed for about 8-12 minutes until the material is uniform and there is no obvious agglomeration phenomenon, and a material that can be used for repair is obtained. Similarly, when stirring, first put the organic compound B and the additive into the stirring equipment for preliminary mixing, and then slowly add the chopped glass fiber, stirring while adding, pay attention to the state of the material, and ensure that the fiber is evenly dispersed in the material, and there is no fiber agglomeration or precipitation. Apply or pour the prepared repair material to the damaged or cracked part of the inspection well seat. For smaller cracks, the application method can be used, and for larger damaged areas, the pouring method can be used. During the application or pouring process, special tools should be used to compact and smooth the material so that it fits the substrate surface fully. For application construction, tools such as spatulas can be used to evenly apply the material to the cracks or damaged surfaces to ensure that the material can fill all gaps and is in close contact with the substrate surface. For pouring construction, the material can be slowly poured into the larger damaged area with the help of tools such as funnels, and the inspection well seat can be gently vibrated to help the material better fill every corner, and then the surface is smoothed with tools to make it flush with the surrounding substrate surface.

[0042] Allow the repair material to cure naturally at room temperature. The curing time varies slightly depending on the ambient temperature and humidity, generally 24-48 hours. During the curing process, avoid external interference on the repaired part to ensure that the material can fully cure to form a stable structure. Warning signs can be set up around the repaired part to prevent pedestrians and vehicles from accidentally touching it. At the same time, pay attention to the changes in ambient temperature and humidity during the curing process. If the ambient temperature is too low or the humidity is too high, it may affect the curing speed and curing effect. Consider taking appropriate insulation or dehumidification measures, such as covering with plastic film, to promote the normal curing of the repair material.

[0043] In order to fully verify the performance differences between the repair materials of the two solutions of the present invention and the existing common repair materials, a series of detailed comparative tests were carried out, covering multiple aspects such as bonding strength, compressive strength, flexural strength, elastic modulus, water resistance and environmental protection performance.

[0044] The repair materials of solution 1 and solution 2 of the present invention were prepared, and several common road inspection well seat repair materials on the market were selected as comparison samples. According to the standard test methods and specifications, the corresponding test specimens were made to ensure that the size, shape, manufacturing process and other conditions of each specimen were consistent to ensure the accuracy and comparability of the test results.

[0045] For the bonding strength test, the tensile test method is used. The repair material is applied to a test block that simulates the inspection well seat base. After solidification, a tensile force is applied at a certain rate through a tensile testing machine until the specimen is destroyed. The tensile force value at the time of destruction is recorded, and the bonding strength is calculated based on the bonding area of ​​the test block.

[0046] The compressive strength test is to place the prepared cube specimen on the pressure testing machine, apply pressure at a constant loading rate until the specimen is broken, record the maximum pressure value at the time of failure, and then calculate the compressive strength based on the size of the specimen. The flexural strength test uses the three-point bending test method, placing the rectangular specimen on the test device, applying a concentrated load to the middle of the specimen, gradually increasing the load at a certain loading rate until the specimen breaks, and recording the load value at the time of fracture, and then calculating the flexural strength.

[0047] The elastic modulus test is carried out while the compressive strength test is being carried out. The deformation of the specimen is measured at different load stages and the result is calculated according to the elastic modulus calculation formula.

[0048] The water resistance test is to soak the specimen in water for 24 hours, take it out and wipe off the surface moisture, and then conduct a compressive strength test again. The strength retention rate is calculated based on the change in compressive strength before and after soaking to evaluate the water resistance of the material.

[0049] The environmental performance test is based on relevant environmental standards and testing methods to test the various components in the repair materials to determine whether they meet environmental protection requirements. The main testing indicators include volatile organic compound (VOC) content, heavy metal content, etc.

[0050]

[0051] From the perspective of bonding strength, the repair materials of the two solutions of the present invention both show obvious advantages. The bonding strength of existing common repair materials is generally between 1.0-1.3MPa, while the bonding strength of the repair material of solution one of the present invention reaches 2.5MPa, and the repair material of solution two is as high as 2.8MPa. This is mainly due to the special functional group structure of the organic compounds A and B used in the present invention. Their interaction mechanism with the surface of the well base substrate effectively improves the bonding force between the material and the substrate, making the repaired structure more solid and less prone to loosening, falling off, etc.

[0052] Example 4

[0053] Material composition and function (I) Component A

[0054] Component A, as a polyol component, plays a key role in the entire material system. It is specifically composed of bio-based polyols, short-chain polyethers, epoxy-modified polyethers, catalysts and other additives.

[0055] Bio-based polyol: Its content is between 60-80 parts. Its main function is to provide a certain strength to the material and effectively improve water sensitivity. In practical applications, this helps the manhole cover maintain stable performance in different humidity environments and reduce performance degradation caused by water erosion.

[0056] Short-chain polyether: accounting for 10-20 parts, can provide lower viscosity, making it easier to stir the components evenly during mixing, while also improving the reaction curve to ensure that the entire chemical reaction process proceeds more smoothly and efficiently.

[0057] Epoxy modified polyether: also accounts for 10-20 parts, it contributes significantly to the bonding of the substrate and the strength of the main body. Good bonding performance allows the manhole cover material to be tightly combined with surrounding structures such as the manhole ring, while sufficient main body strength ensures the stability of the manhole cover when it is subjected to external forces such as vehicle loads.

[0058] Catalyst: The dosage is 0.01-0.20 parts. In this material system, an organic tin catalyst can be selected, such as dibutyltin dilaurate (chemical formula: C 32 H 64 O 4 Sn). Its main function is to accelerate the chemical reaction between the components and enable the material to reach the expected performance state faster. Organic tin catalysts can effectively reduce the activation energy of the reaction, allowing the reaction to proceed faster under relatively mild conditions, thereby improving production efficiency and ensuring the uniformity of material performance.

[0059] Water absorbent: The content is 1-5 parts, and montmorillonite (chemical formula: (Al, Mg) can be used 2 (Si 4 O 10)(OH) 2 ·nH 2 O) As a water absorbent. Montmorillonite has a large specific surface area and interlayer adsorption capacity, which can absorb a small amount of water that may be mixed into the system, further ensuring that the material performance is not disturbed by water. It can prevent water from reacting adversely with other active components by absorbing water in its interlayer structure, thereby maintaining the stability of the material and the consistency of its performance.

[0060] (II) Component B

[0061] Component B is modified MDI, and its NCO mass fraction is 28-30%. Specific products include BASF Lupranate MM103, Huntsman Suprasec 2020 or Dow Isonate 143L. It mainly provides a balance between toughness and fluidity in the material system, so that the manhole cover material has sufficient toughness to resist external impact without cracking, and can maintain good fluidity during construction, which is convenient for filling the gap between the manhole cover and the well ring.

[0062] (III) Component C

[0063] Component C is composed of heavy calcium powder, quartz powder, rubber powder, water, etc., which provide multi-faceted performance guarantees for the system. Heavy calcium powder (100-200 mesh): The content is between 50-70 parts, which is heavy calcium carbonate powder (chemical formula: CaCO 3 ), which can provide a certain strength to the material and enhance the bearing capacity of the manhole cover so that it can withstand the pressure of passing vehicles.

[0064] Quartz powder (100-200 mesh): 10-20 parts, quartz powder (chemical formula: SiO 2 ) has high hardness and wear resistance, which can effectively improve the wear resistance of the manhole cover material, extend the service life of the manhole cover, and reduce the wear caused by long-term vehicle rolling and friction.

[0065] Rubber powder (40-80 mesh): accounts for 10-20 parts. The addition of rubber powder brings a certain elasticity and expansion to the material. The elasticity allows the manhole cover to have a certain buffering effect when it is hit by a vehicle, reducing damage to itself and surrounding structures; the expansion helps the manhole cover fit better with the well ring after installation, fills the gap, and prevents rainwater, debris, etc. from entering the well.

[0066] Water: The dosage is 0.1-0.3 parts. Although the content is small, water has an important influence on the expansion and other properties of the material in the entire system.

[0067] 3. Material preparation method

[0068] (I) Preparation of component A

[0069] First, the components such as bio-based polyols, short-chain polyethers, epoxy-modified polyethers, dibutyltin dilaurate catalysts and montmorillonite water absorbents are mixed and stirred according to the proportions to make them fully mixed. Then the mixed component A is heated to 105℃-120℃ for vacuum dehydration. This step can effectively remove the moisture that may be contained in the material and avoid the influence of moisture on subsequent reactions and material properties. After completing the vacuum dehydration, component A is cooled to room temperature in a dry environment and finally packaged in a sealable plastic bottle or plastic barrel to ensure its stability during storage and transportation.

[0070] (II) Preparation of component B

[0071] Component B is modified MDI, which can be directly packaged in sealable plastic bottles or plastic barrels. During the packaging process, it is necessary to ensure that it is well sealed to prevent it from coming into contact with external moisture and other substances and reacting.

[0072] (III) Preparation of Component C

[0073] First, stir and mix the other components except water, such as heavy calcium powder, quartz powder, rubber powder, etc., and then heat them to 105℃-120℃ for vacuum dehydration to remove any moisture. Then cool them to room temperature in a dry environment and finally package them in sealed plastic bags. Before sealing the package, add a certain amount of water according to the ratio to ensure that the moisture content in component C is precisely controllable, thus laying the foundation for the subsequent control of the expansion of the entire mixture.

[0074] IV. On-site use and performance control of materials

[0075] (I) On-site use

[0076] At the construction site, mix components A, B, and C in a mass ratio of 2:1:6. First, pour components A and B into a container and stir evenly, then add component C and continue stirring until the entire mixture is stirred evenly before use.

[0077] (II) Key points of performance control

[0078] In the entire material system, since the MDI in component B reacts with water and releases carbon dioxide, if the moisture content in the mixture is not properly controlled, the volume expansion problem will occur in the stirred mixture. On the one hand, excessive expansion will cause the manhole cover to shift, affecting the accuracy and stability of its installation position; on the other hand, it will cause the strength and toughness of the mixture to decrease, and it will not be able to meet the performance requirements of the manhole cover in actual use, such as load-bearing and impact resistance. Therefore, the present invention first heats and vacuum dehydrates component C to eliminate the original unquantifiable moisture therein, and then adds a certain amount of water and seals it, thereby ensuring that the moisture content in the mixture system is completely controllable. In this way, it can ensure that the mixture has a certain amount of expansion, so that the gap between the manhole cover and the well ring is completely filled, achieving a good sealing and installation effect, and will not affect the strength and toughness of the mixture, ensuring the stability of the performance of the manhole cover in the subsequent use process, and effectively solving the problems of mixture performance fluctuations and manhole cover installation and use caused by moisture.

[0079] In actual application, the curing time of the mixture varies according to the different construction environment temperatures on site. At 20-30°C, the mixture generally takes 15-20 minutes to initially set, 30-40 minutes to harden, and 60-90 minutes for vehicles to pass. Construction personnel can reasonably arrange the construction schedule based on these curing time characteristics to ensure the smooth installation of the manhole cover.

[0080] In summary, the new manhole cover material and its preparation and application method of the present invention provide a feasible solution for improving the performance and stable use of manhole covers through reasonable component design, precise preparation process and effective performance control measures, and have good application prospects.

Claims

1. A road inspection well seat repair material, characterized in that: It comprises an organic compound A and an organic compound B, wherein the organic compound A is a compound having a chemical formula of C 10 H 12 The chemical structure of O3S's mercaptophenyl ester alcohol contains mercapto, benzene ring and ester group. The organic compound B is a compound having a chemical formula of C 12 H 27 The molecular structure of aminooctyl ether amine of NO includes amino group, ether bond and long-chain alkyl group.

2. The road inspection well seat repair material according to claim 1, characterized in that: The mercaptophenyl ester alcohol is prepared by reacting p-mercaptophenol with methyl acrylate in an organic solvent in the presence of an alkaline catalyst, the reaction temperature is controlled at 40-60° C., and the reaction time is 3-5 hours.

3. The road inspection well seat repair material according to claim 1, characterized in that: The aminooctyl ether amine is prepared by reacting n-octanol and ethanolamine as raw materials under the action of an acidic catalyst under reflux conditions, the reaction temperature is about 120-140° C., and the reaction time is 6-8 hours.

4. The road inspection well seat repair material according to claim 1, characterized in that: The organic compound A is replaced by the following components in mass ratio: 60-80 parts of bio-based polyol, 10-20 parts of short-chain polyether, 10-20 parts of epoxy-modified polyether, and 1-5 parts of water absorbent; the organic compound B is replaced by modified MDI with an NCO mass fraction of 28-30%.

5. The road inspection well seat repair material according to claim 1, characterized in that: The repair material also includes nano calcium carbonate, the particle size of which is 20-50 nm, and the added amount is 5-10% of the total mass of the mixture of compound A and compound B.

6. The road inspection well seat repair material according to claim 1, characterized in that: The repair material also includes an antioxidant, which is a hindered phenol antioxidant, and the added amount is 0.5-1% of the total mass of the mixture of compound A and compound B.

7. The road inspection well seat repair material according to claim 1, characterized in that: The mixing ratio of the compound A and the compound B is 3:2-4:

1.

8. A method for repairing a road inspection well seat using the environmentally friendly repair material according to any one of claims 1 to 6, characterized in that: It also includes material mixing and construction steps: stir the compound A and compound B, nano calcium carbonate and antioxidant mixed in proportion at the construction site for 8-10 minutes to make them evenly dispersed, then pour them into a special mold or directly apply them to the repaired part of the inspection manhole seat with a thickness of 2-4 cm, and ensure that the material fits tightly to the surface of the original inspection manhole seat without bubbles and gaps.